Prognostic value of 18F‐fluorodeoxyglucose positron emission tomography/computed tomography in patients with cutaneous angiosarcoma: A retrospective study of 18 cases. Issue 9 (31st March 2017) - Umemura, Hiroshi; Yamasaki, Osamu; Kaji, Tatsuya; Hamada, Toshihisa; Otsuka, Masaki; Asagoe, Kenji; Iwatsuki, Keiji
Abstract: Cutaneous angiosarcoma (CAS) is a rare soft tissue sarcoma with rapid growth and poor prognosis. We retrospectively analyzed the data of 18 patients with CAS who underwent 18 F‐Fluorodeoxyglucose positron emission tomography/computed tomography (FDG PET/CT) at the initial visit to the Department of Dermatology, Okayama University Hospital from September 2006 to March 2016. In the univariate survival analysis, patients with high standardized uptake values (SUVmax ) of the primary tumor showed significantly poorer prognosis than those with low SUVmax . Early assessment of prognosis using PET/CT may predict patient survival and is useful in the selection of therapeutic strategies.